Mindfulness experiences of university staff in New Zealand : an integrated workplace mindfulness framework : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, Auckland, New Zealand - Shahbaz, Wahab (Massey University, 2021)
Research on and the practice of mindfulness is increasing in the organisational context. It is generally understood that mindfulness is a human ability or practice which guides the cognitive and psychological processes of employees and informs their decisions and actions in everyday life. Many organisations thus offer mindfulness training programmes to their employees in order to obtain workplace benefits such as improving well-being, inter-relationships, and performance. Much existing work on mindfulness in the organisational context has focused on the consequences of mindfulness interventions and the benefits that the mindful individual can bring to their work. Despite the positive relationship that research has shown between mindfulness and workplace functions, we still know little about how employees actually experience mindfulness. Such an understanding is important to advance organisational strategies and training inventions to promote health, well-being, and the productivity of employees. University staff experience considerable stress at work, and in response many universities around the world have made mindfulness sessions available as part of their staff support practices. Thus, they were an appropriate group to research regarding mindfulness experiences. The purpose of this research was thus to explore the mindfulness experiences of university staff in order to understand their experiences in more depth. In particular, using positive organisational behaviour (POB) as a theoretical lens and conservation of resource (COR) as an additional tool, this thesis focuses on aspects of mindfulness experience that can give insight into how employees enact mindfulness, for example: their everyday practices of mindfulness; their perspectives about workplace outcomes of mindfulness; and what employees perceive to be the facilitating and hindering factors of mindfulness. The research addressed three key research questions: i) how do staff experience mindfulness in the university?; ii) how and why might mindfulness impact on the workplace functions of university staff?; and iii) what individual and workplace factors facilitate or hinder the mindfulness experiences of university staff? To meet the research objectives of this study, a qualitative approach was based on phenomenological enquiry. In-depth, semi-structured interviews were conducted with 28 faculty and administrative staff from different universities in New Zealand who had attended mindfulness-based training programmes and/or who practised mindfulness. Based on a qualitative thematic analysis of interview material, an integrated workplace mindfulness framework was developed that helps us to understand how employees perceive their mindfulness experiences and practices. First, the framework presents five different kinds of mindfulness-related experiences including formal practices, informal moments, mindful interactions, a state of awareness, and the state of being present. These mindfulness experiences help us to comprehend how staff operationalise mindfulness in the university environment. Second, the framework provides a range of well-being, relationship, and performance-related consequences of mindfulness to address the question relating to the workplace outcomes of mindfulness. Third, the framework elaborates on different mechanisms and functions that explain the relationship between mindfulness and workplace outcomes such as attentional stability, psychological detachment, self-regulation, attentional control, and cognitive flexibility. The mechanisms help us to understand why mindfulness affects workplace functions. Finally, to address the question relating to individual and workplace factors that facilitate or hinder mindfulness, the framework highlights various factors including individual efforts, communal support, and sectoral culture that can influence the application of workplace mindfulness in the university setting. This study contributes to knowledge by providing a comprehensive framework which will assist in the refinement and development of many branches of mindfulness research. In particular, the study discusses relevant aspects of POB and COR to draw out implications for operationalisation, outcomes, mechanisms, and factors affecting workplace mindfulness in the university setting. Practice contributions are also provided. The thesis has implications for the refinement of training practices and organisational efforts in the university sector as well as in other professions to optimise mindfulness programmes for employees’ well-being and productivity.
Appendix C has been removed for copyright reasons.
Keywords: Employee health promotion; Mindfulness (Psychology); Universities and colleges; New Zealand; Employees; Attitudes; 350507 Workplace wellbeing and quality of working life